In Vitro Activation and Inhibition of Recombinant EGFR Tyrosine Kinase Expressed in Escherichia coli - Jihene Elloumi-Mseddi; Karim Jellali; Sami Aifa (The Scientific World Journal)
The present work concerns the heterologous expression of the intracellular domain harbouring the tyrosine kinase activity of the epidermal growth factor receptor (EGFR). Protein expression was improved thanks to the deletion of a 13-amino acid peptide of the juxtamembrane region (JM). The recombinant proteins were produced as a glutathione S-transferase (GST) fusion in Escherichia coli, and the solubilisation was performed by sarkosyl addition during extraction. The produced proteins spontaneously dimerize allowing the activation of the tyrosine kinase domain in the presence of [γ-32P]ATP. The activity assay has revealed the autophosphorylation of EGFR proteins which was decreased in the presence of genistein. Our system could facilitate the screening of EGFR inhibitors without the need of adding an exogenous substrate.